2023
DOI: 10.3389/fpls.2022.1080635
|View full text |Cite
|
Sign up to set email alerts
|

Amassing of heavy metals in soils, vegetables and crop plants irrigated with wastewater: Health risk assessment of heavy metals in Dera Ghazi Khan, Punjab, Pakistan

Abstract: Human health is the main concern related to use of crop products irrigated with contaminated irrigation sources. Present research has been conducted to explore heavy metal status of sewage and industrial wastewater being used up for irrigation purpose in the peri-urban areas of the district Dera Ghazi Khan which has not been explored widely before. The analysis also followed heavy metal detection in the subsequent irrigated soil and vegetables/crop plants in relation to assessment of health risk to the consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
0
11
2
1
Order By: Relevance
“…However, still, their function is not fully understood. GLPs are expressed in all types of tissues (flowers, seeds, roots, stems, leaves, and embryos) by playing a pivotal role against diverse environmental stresses. , Previously, among abiotic stresses, they were found effective against heavy metals, , drought, , salt, , desiccation, heat, , abscisic acid (ABA), and UV radiation acclimation mediated by methylation in the promoter region as observed in rice . Among biotic stresses, they were active against herbivore-induced damage, Sclerotinia sclerotiorum (S.…”
Section: Introductionmentioning
confidence: 99%
“…However, still, their function is not fully understood. GLPs are expressed in all types of tissues (flowers, seeds, roots, stems, leaves, and embryos) by playing a pivotal role against diverse environmental stresses. , Previously, among abiotic stresses, they were found effective against heavy metals, , drought, , salt, , desiccation, heat, , abscisic acid (ABA), and UV radiation acclimation mediated by methylation in the promoter region as observed in rice . Among biotic stresses, they were active against herbivore-induced damage, Sclerotinia sclerotiorum (S.…”
Section: Introductionmentioning
confidence: 99%
“…Boron is an essential micronutrient for the growth of plants, and it can facilitate the proper growth and development of plants in little quantity. The deficiency of these micronutrient can lead to the reduction of physiological and metabolic process; however, sufficient amounts of their presence in food treats various health problems. Taskin and Gunes reported that accessibility of these micronutrients in calcareous and alkaline soil becomes inadequate due to the restricted mobility in the plant body which causes reduction in plant growth. In the present study improvements in the studied traits under the applied treatments of micronutrients indicated the efficiency of foliar applied nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Wheat (Triticum aestivum L.) is the most important crop in the world after rice and maize with a total production of 765 million tons, covering 216 million hectares. The wheat grain contains 20% food calories and 55% carbohydrates and is a chief source of food across the globe. However, besides the risks of climate change and increased population, wheat producers and breeders are facing bigger challenges of malnutrition and food insecurity. Furthermore, it is believed that a substantial increase in the production of agricultural crops after green revolution has led to a gradual decline in the nutritional quality of elite high-yielding cereal crops, particularly wheat. An exceptional rise in atmospheric CO 2 up to 420 ppm has directly affected the carbon assimilation, the result being decreased accumulation of both grain micro- and macronutrients. …”
Section: Introductionmentioning
confidence: 99%